Development of Automatic Equipment for Washing and Nondestructive Inspection of Stud Bolt. (28th December 2020) - Kwak, H. S.
Abstract : Low-pressure steam turbines in a power plant are required to operate at high temperatures and under high pressures to achieve better energy utilization and better performance. Higher operating temperatures accelerate the rate of oxidation and sludge formation, so the steam turbine is periodically inspected including strict examination of the stud bolts, and it is necessary to clean the bolts by removing sludge from their screw threads. In the conventional cleaning process, the sludge has been removed by manual cleaning, which is labor-intensive and time-consuming. Therefore, this study developed automatic equipment for washing and nondestructive inspection of stud bolts using theoretical analysis and finite element analysis (FEA). An optimal clamp load to prevent sliding of the roller was calculated, and a structural analysis of the equipment under operating conditions was conducted. An optimal washing condition to maximize cleaning efficiency was proposed using design of the experiment and verified by performing washing test of prototype.